Antibacterial properties and electrical characteristics of multifunctional metal composite fabrics. (March 2016) - Yu, Zhi-Cai; Lu, Yan-Hua; He, Hua-Ling; Zhang, Jian-Fei; Lou, Ching-Wen; Chen, An-Pang; Lin, Jia-Horng
In this research, a hollow spindle spinning machine was used to manufacture the multifunctional metal hybrid yarns with stainless steel wire (SSW) as core material, antibacterial nylon (AN) filaments and bamboo charcoal polyester filaments (BC-PETs) as inner and outer wrapped yarn, respectively. The wrapping numbers of produced metal hybrid yarns varied from 8.0 to 15.5 turns/cm. Furthermore, metal composite woven fabrics were fabricated with the metal hybrid yarns as weft yarns and PET filaments as warp yarns on a loom. These woven fabrics were evaluated in terms of far infrared (FIR) emissivity, anion density, electromagnetic shielding effectiveness (EMSE) and surface resistance. The antibacterial activity of the woven fabrics was assessed against both Staphylococcus aureus and Escherichia coli according two test methods AATCC100-2004 and 90-2011, respectively. The wrapping numbers showed a significant influence on the FIR emissivity and anion density of the produced woven fabrics. The presence of SSW in the hybrid yarns decreased the surface resistance and improved the EMSE of the woven fabrics. EMSE measurement showed that FH-15.5 woven fabrics with 0°/90°/0°/90° lamination angles displayed a better electromagnetic shielding behavior than with 0°/ 45°/90°/−45° lamination angles.